The possibilities of the digital environment for the formation of competencies of younger students - Selezneva A. E. (The Topical Issues of the Humanities and Social Sciences: from Theory to Practice, 2024)
Abstract: the article examines the possibilities of using the components of the digital educational environment in teaching for younger students to form "universal competencies" in extracurricular activities. The deficits in the level of readiness to use digital educational resources in education among students in grades 3-4 are considered. A modular online course on the Stepik platform has been implemented in extracurricular activities for primary school children, allowing them to form universal competencies and a new literacy in the field of traffic rules, in the organization of detachments of young traffic inspectors.
Keywords: компетенции; начальная школа; primary school; курс; competencies; цифровая среда; ЮИД; Keywords: digital environment; course; UID